The economic contribution of protected natural areas: benefits from human use - Hughes, Michael; Carlsen, Jack (Curtin University, 2011)
This paper presents two examples from Australia where economic contributions from human use of protected natural areas have been quantified and a clear argument for increased investment in management resources generated.